2012
DOI: 10.1017/s096025851200013x
|View full text |Cite
|
Sign up to set email alerts
|

Breaking physical dormancy of Cassia leptophylla and Senna macranthera (Fabaceae: Caesalpinioideae) seeds: water absorption and alternating temperatures

Abstract: This study analysed the anatomical structure of the seed coats, identified the location of water uptake and evaluated the effects of alternating temperatures and heat treatment on the breaking of physical dormancy of two species of Fabaceae (Caesalpinioideae), Cassia leptophylla and Senna macranthera, from the Atlantic forest of Brazil. The seed coats of both species consisted of a cuticle (extra-hilar region) or remaining funicle region (hilar region), subcuticular layer, palisade layer with lignin, osteoscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 30 publications
2
24
0
6
Order By: Relevance
“…La impermeabilidad de la cubierta se debe a la presencia de una o más capas de células en empalizadas (células de Malpighi) impregnadas con sustancias hidrofóbicas (Rolston, 1978;Baskin & Baskin, 2004;Venier et al, 2012). Se ha documentado que el ingreso del agua ocurre en una región anatómica especializada (como el lente en Fabaceae), que en condiciones favorables, actuaría como una válvula higroscópica permitiendo la imbibición de las semillas (De Paula et al, 2012;Baskin & Baskin, 2014). En condiciones naturales, se ha sugerido que la exposición de las semillas a altas temperaturas o a temperaturas fluctuantes serían los responsables de la salida de dormición (Vazquez-Yañes & Orozco-Segovia, 1982), mientras que en condiciones de laboratorio la escarificación mecánica, térmica y química, así como el almacenamiento en seco, las bajas temperaturas y las altas presiones atmosféricas, facilitarían la salida de dormición de las semillas (ver Baskin & Baskin, 2014).…”
Section: Introductionunclassified
“…La impermeabilidad de la cubierta se debe a la presencia de una o más capas de células en empalizadas (células de Malpighi) impregnadas con sustancias hidrofóbicas (Rolston, 1978;Baskin & Baskin, 2004;Venier et al, 2012). Se ha documentado que el ingreso del agua ocurre en una región anatómica especializada (como el lente en Fabaceae), que en condiciones favorables, actuaría como una válvula higroscópica permitiendo la imbibición de las semillas (De Paula et al, 2012;Baskin & Baskin, 2014). En condiciones naturales, se ha sugerido que la exposición de las semillas a altas temperaturas o a temperaturas fluctuantes serían los responsables de la salida de dormición (Vazquez-Yañes & Orozco-Segovia, 1982), mientras que en condiciones de laboratorio la escarificación mecánica, térmica y química, así como el almacenamiento en seco, las bajas temperaturas y las altas presiones atmosféricas, facilitarían la salida de dormición de las semillas (ver Baskin & Baskin, 2014).…”
Section: Introductionunclassified
“…However, they observed that depending on the time exposed to sulphuric acid, or in the field, the lens and extra-hilar region also become permeable to water. Another structure that has been mentioned as being important to the entrance of water in seeds of Cassia (Fabaceae), which are physically dormant, is the micropyle (Bhattacharya, & Saha, 1990;Paula, Delgado, Paulilo, & Santos, 2012). For S. tomentosa and E. speciosa in the present work, it was interesting to notice that when only the micropyle was blocked, in scarified seeds, the water uptake was inhibited until the second and fourth day (respectively) of seed incubation.…”
Section: Discussionmentioning
confidence: 50%
“…In the case of O. macrocalyx, this region is characterized by the fractured hilar slit in recently formed seeds, and by the possible presentation of a lens (Figure 4). These structures have been shown to be important zones for water imbibition in legume seeds (De Paula et al 2012). High temperatures also allow degradation of lipids in the seed coat, facilitating water permeability (Zeng et al 2005), a process that is further assisted by the thinner tissue present in this seed region (Varela & Albornoz 2013).…”
Section: Discussionmentioning
confidence: 99%